2020
DOI: 10.1136/bmjspcare-2019-001986
|View full text |Cite
|
Sign up to set email alerts
|

Mental healthcare and palliative care: barriers

Abstract: ContextPsychological symptoms are common among palliative care patients with advanced illness, and their effect on quality of life can be as significant as physical illness. The demand to address these issues in palliative care is evident, yet barriers exist to adequately meet patients’ psychological needs.ObjectivesThis article provides an overview of mental health issues encountered in palliative care, highlights the ways psychologists and psychiatrists care for these issues, describes current approaches to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 20 publications
0
19
0
2
Order By: Relevance
“…The teams are supposed to help and support the FPs-a practice explored in a Canadian study focusing on "institutionrelated barriers (i.e., the healthcare system), interest-related barriers (i.e., motivations of stakeholders) and Idea-related barriers (i.e., values of stakeholders and information/ research), on sociopolitical barriers" (60). Research on barriers in palliative care has found that patient well-being is improved by palliative teams where psychologists and psychiatrists are core members of the treatment team (61). That is why integrated care teams are needed to ensure high quality palliative care at home.…”
Section: Barriers To Home Palliative Carementioning
confidence: 99%
“…The teams are supposed to help and support the FPs-a practice explored in a Canadian study focusing on "institutionrelated barriers (i.e., the healthcare system), interest-related barriers (i.e., motivations of stakeholders) and Idea-related barriers (i.e., values of stakeholders and information/ research), on sociopolitical barriers" (60). Research on barriers in palliative care has found that patient well-being is improved by palliative teams where psychologists and psychiatrists are core members of the treatment team (61). That is why integrated care teams are needed to ensure high quality palliative care at home.…”
Section: Barriers To Home Palliative Carementioning
confidence: 99%
“…A high comorbidity of mental illness is present in most patients with chronic medical problems, providing many opportunities for clinical training sites. Current evidence supports integrated models for primary care, 43 HIV, 44,45 cardiology, 46 oncology, 47,48 women's health (obstetrics and gynecology), 49 transplantation, 50 weight loss surgery, 51 epilepsy clinics, 52 palliative care, 53 and pain clinics. 54 There are other clinical sites where patients are known to have high comorbidity of psychiatric issues, but to date, there are no reports on colocation or collaboration; these include rheumatology, 55 endocrinology, 56 dermatology, 57 and plastic surgery.…”
Section: Training Sitesmentioning
confidence: 99%
“…In the UK, national guidance recommends four levels of psychological support (Figure 1), with those with more complex needs requiring support from counsellors, psychologists, psychotherapists, mental health nurses or psychiatrists (National Institute & for Health & Care Excellence, 2004). This is seen as best practice both nationally (National Institute for Health & Care Excellence, 2017) and internationally (O'Malley, Blakley, Ramos, Torrence, & Sager, 2020; Payne & Junger, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This means patients and family carers may not receive the type of support they require (Oechsle, 2019; Wang, Molassiotis, Chung, & Tan, 2018). Psychological symptoms can be underestimated as they are assumed to be expected in this population (O'Malley et al., 2020). Symptoms such as fatigue may be mistaken for side effects of underlying disease or treatment (Boakye et al., 2019), and it can be unclear whose role it is to provide psychological care (Kozlov et al., 2018).…”
Section: Introductionmentioning
confidence: 99%